1987
DOI: 10.1002/eji.1830170907
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the W6/32 HLA epitope by cells of rat, mouse, human and other species: critical dependence on the interaction of specific MHC heavy chains with human or bovine β2‐microglobulin

Abstract: The HLA class I epitope W6/32 is conformationally dependent on both heavy chain and beta 2-microglobulin (beta 2M). Previously, the W6/32 epitope has been detected in humans and other primates as well as from bovine sources. Two controversial reports suggest the W6/32 epitope is constitutively expressed by either normal or transformed murine cells expressing the Db allele. Here we show that the appearance of the W6/32 epitope in murine cells results from the association of either the Db or Kd gene products wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…One explanation for this result is that the in vitrotranslated ␤ 2 m continues to fold in the presence of this modest concentration of DTT and can also associate with preexisting unlabeled canine class I heavy chains that reside in the microsomes used for translation. Indeed, interspecies exchange of ␤ 2 m is a common occurrence (25,26). At no time does HLA-DR1␣ coprecipitate with class I molecules or US2͞US11.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this result is that the in vitrotranslated ␤ 2 m continues to fold in the presence of this modest concentration of DTT and can also associate with preexisting unlabeled canine class I heavy chains that reside in the microsomes used for translation. Indeed, interspecies exchange of ␤ 2 m is a common occurrence (25,26). At no time does HLA-DR1␣ coprecipitate with class I molecules or US2͞US11.…”
Section: Resultsmentioning
confidence: 99%
“…Values of PϽ0.05 were considered significant. 33 Dose-response experiments (mitogenic effect of increasing W6/32 concentration) showed that 1 g/mL W6/32 mAb was optimal to trigger [ 3 H]thymidine incorporation in cultured SMCs ( Figure IVA in the online-only Data Supplement) and cell proliferation (increased cell number), as assessed by cell counting ( Figure IVB in the online-only Data Supplement). This W6/32 concentration (1 g/mL) exhibited no cytotoxic effect ( Figure IVC in the online-only Data Supplement) and was therefore utilized throughout the experiments (unless otherwise indicated).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Human mAbs (40) were selected that are operationally alloantigen-specific on Daudi cells (specificities are noted, Daudi alleles boldface): GV5D1 (A1, A9; IgG), SN230G6 (A2, B17, B57, B58; IgG), VP5 G3 (A11, A25, A26, A66; IgM), TRA2G9 (Cw1, Cw3, Cw4, Cw*1402; IgM), BVK1F9 (B8; negative IgG control), and BVK 5B10 (B8; negative IgM control). Peptides GILG-FVFTL from the influenza virus matrix glycoprotein 58 -66 (M1-Flu58 -66, flu), and AAGIGILTV from the melanoma Ag Melan-A/MART-1 [27][28][29][30][31][32][33][34][35] (Mart) are two well-known HLA-A2 ligands displaying high and low affinity, respectively (41), and major T cell epitopes. The HLA-B27 ligand FRYNGLIHR was used as a negative control in in vitro assembly assays.…”
Section: Abs and Protein Biochemistrymentioning
confidence: 99%
“…4C, compare the two bottom panels). mAbs to ␤ 2 m (BBM1 and Namb-1) did not stain Daudi-A2 cells grown in the A; lanes 1-30) or chased for 120 min before lysis (B; lanes [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Aliquots of the lysates were incubated as indicated, either at 4°C (lanes 1-8, 17-23, 31-35, and [41][42][43][44][45] or at 37°C (lanes 9 -16, 24 -30, 36 -40, and 46 -50) …”
Section: W6/32-reactive Free Heavy Chains Are Receptive To Peptide Anmentioning
confidence: 99%
See 1 more Smart Citation